PENGARUH BLENDED LEARNING BERBASIS COOPERATIVE LEARNING PADA PERKEMBANGAN KOGNITIF ANAK USIA DINI - M.Tsaqibul Fikri; Hidayah (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2021)
The blended learning model based on cooperative learning can be an alternative in developing early childhood cognitive, using a variety of interesting activities so that children are able to solve problems creatively. This study aims to analyze the significance of the effect of the cooperative learning-based blended learning model on the cognitive development of children aged 3-4 years. The method used in this study is Pre-experimental with a one-group pretest-posttest design. This research was carried out at KB Al Hikmah, Cengkong Village, Parengan District, Tuban Regency. The time to carry out this research is on 25-27 February 2021. The population in this study amounted to 18 children. The sampling technique used was non-probability sampling. The data collection technique of this research used observation and documentation. The data analysis technique used table analysis, non-parametric uni analysis and simple linear regression test. The results of this study indicate that there is an effect of the blended learning model based on cooperative learning on the cognitive development of children aged 3-4 years before being given blended learning activities and after being given blended learning activities.